Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/s004170000191
|View full text |Cite
|
Sign up to set email alerts
|

Optical cylinder designs to increase the field of vision in the osteo-odonto-keratoprosthesis

Abstract: Results demonstrate that it is possible to significantly increase the theoretical maximum visual field through OOKP optical cylinders. Such designs will improve the visual rehabilitation of patients undergoing this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Previous it has been shown that the Italian cylinder has a maximum theoretical visual field of 76 o and further modifications can increase this to a maximum of 90 o . 10 Increasing the diameter of the cylinder will help to improve the visual field but this is limited by the diameter of the available root of the tooth. However, if the cylinder diameter is too large then visual function may be affected by glare.…”
Section: Discussionmentioning
confidence: 99%
“…Previous it has been shown that the Italian cylinder has a maximum theoretical visual field of 76 o and further modifications can increase this to a maximum of 90 o . 10 Increasing the diameter of the cylinder will help to improve the visual field but this is limited by the diameter of the available root of the tooth. However, if the cylinder diameter is too large then visual function may be affected by glare.…”
Section: Discussionmentioning
confidence: 99%
“…Two-piece designs based on an inverted telephoto principle gave theoretical field angles over 120°. Aspheric surfaces were shown to improve the off-axis image quality while maintaining a potential visual acuity of at least 6/6 [6].…”
Section: Discussionmentioning
confidence: 99%
“…It uses the patient's own tooth and alveolar bone to support an optical cylinder. The two major drawbacks of OOKP are the complexity of the surgery and the narrow field of vision [6].…”
mentioning
confidence: 99%
“…5,6,10 However, as technology moves forward, new-generation 2-piece keratoprostheses may also offer the advantages of improved biointegration, ability to measure intraocular pressure, reduced retroprosthetic membrane formation, and increased visual field. [27][28][29][30][31][32] The FDA has recently approved the AlphaCor intracorneal keratoprosthesis for marketing in the United States. Multicenter clinical trials have been in progress for more than 3 years in Australia and Southeast Asia with outcomes reported in 45 patients.…”
Section: Discussionmentioning
confidence: 99%